The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3892/mmr.2021.12204
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces apoptosis by inhibiting BCAT1 expression and mTOR signaling in cytarabine‑resistant myeloid leukemia cells

Abstract: Cytarabine is a key chemotherapy drug for treating leukemia; however, chemotherapy-induced multidrug resistance is a major cause of therapy failure or tumor recurrence. Current medical treatment strategies still cannot address the issue of multidrug resistance phenotypes in the treatment of leukemia. Curcumin counteracts tumor development by inducing apoptosis in cytarabine-resistant acute myeloid leukemia cells. Branched-chain amino acid transaminase 1 (BCAT1), an aminotransferase enzyme, acts on branched-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Curcumin-mediated inhibition of BCAT1 and mTOR triggers apoptosis in leukemia cells. 44 Although most of the studies have focused on apoptosis as a kind of cell death regulated by curcumin in affecting leukemia progression, autophagy is also associated with cell death. It has been shown that curcumin and tetrahydrocurcumin have capacity of inducing both autophagy and apoptosis in reducing progression of leukemia cells and decreasing their survival rate.…”
Section: Curcumin and Leukemiamentioning
confidence: 99%
“…Curcumin-mediated inhibition of BCAT1 and mTOR triggers apoptosis in leukemia cells. 44 Although most of the studies have focused on apoptosis as a kind of cell death regulated by curcumin in affecting leukemia progression, autophagy is also associated with cell death. It has been shown that curcumin and tetrahydrocurcumin have capacity of inducing both autophagy and apoptosis in reducing progression of leukemia cells and decreasing their survival rate.…”
Section: Curcumin and Leukemiamentioning
confidence: 99%
“…The activated BCAT1 cooperated with increased Glu to promote the transamination of BCKA, maintaining the cellular BCAA pool (44). In addition, one study reported that curcumin reduced a-KG levels by inhibiting BCAT1 expression and the mTOR pathway, and finally induced apoptosis in cytarabine-resistant ML cancer cells (45).…”
Section: Bcat1 and Acute Myeloid Leukaemia (Aml)mentioning
confidence: 99%
“…The standard therapeutic approach for AML is cytarabine-based therapy that starts with induction chemotherapy [continuous infusion of cytarabine for 7 days concurrent with short infusions of anthracycline on each of the first 3 days (7+3 regimen)], followed by several cycles of consolidation chemotherapy or allogeneic HSC transplantation ( 3 , 4 ). However, only ~70% of patients receiving standard induction therapy achieve complete remission, and only 40% become long-term survivors ( 3 , 5 ). Older patients with AML exhibit stronger intrinsic resistance and less tolerance to chemotherapy than younger patients, resulting in a poor response to standard induction therapy ( 6 ).…”
Section: Introductionmentioning
confidence: 99%